Evaluasi User Experience pada Kahoot dan Socrative menggunakan Metode User Experience Questionnaire (UEQ) (Studi pada SMKN 3 Malang) - Fauzan Fitranda; Hanifah Muslimah Az-Zahra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
One of the problem experienced by teachers of SMKN 3 Malang in class X-TKJ 1 Digital Simulation and Basic Programming lessons is on student engagement, students sometimes feel bored with repetitive activities temporarily as we know in learning sometimes teachers only provide material on the board or then the projector then makes questions and does it on paper and then collects it. Student engagement has 3 dimensions, namely behavioral engagement (student participation), emotional engagement (student interest in doing something) and cognitive engagement (students' efforts in completing their tasks when learning) (Fredricks et al, 2004). The lack of enthusiasm of students towards learning also affects the willingness of students to pay attention to the material. So that students want to participate in learning and not feel bored, Kahoot and Socrative are educational games that can be a solution. Based on this, recommendations are needed regarding User Experience Kahoot and Socrative by using the User Experience Questionnaire (UEQ) method. There are 6 items assessed in UEQ, namely attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty.